Pertanggungjawaban Pidana Pelaku Tindak Pidana Korupsi Dalam Bentuk Penyuapan (Studi Putusan No 12/Pid.Sus Tpk/2018/Pn Medan) - Saur Sihaloho; Madiasa Ablisar; Mahmud Mulyadi; M. Eka Putra (Iuris Studia: Jurnal Kajian Hukum, 2021)
Corruption can take place anywhere, in state institutions, in private institutions, and also in daily life. Combating corruption requires treatment and prevention in an integrated manner with the proper functioning of the legal system of the law and legal institutions in the criminal justice system. Types of research conducted in this research is normative juridical and the nature of this research is descriptive analysis. The data collection techniques used in this research is through library research. Based on the results of this research criminal liability against corruption is the liability of the offenses committed by the offender. Criminal act committed must meet the elements that have been determined by constitution. Someone will be held accountable for these actions when there is an element in the action against the law and there is no excuse and fault elements must be met in terms of combating corruption. This is due to the principle of liability in criminal law that is not tobe punishment if no fault. Criminal acts and the responsibility of the perpetrators of criminal acts for corruption in the form of bribery based on Decision No. 12 / Pid.Sus.TPK / 2018 / PN Medan where to defendant has been proven legally and convincingly, the defendant is able to be responsible and there is no excuse any fault that may negate or justification which can eliminate the unlawful nature of the act, the criminal liability for acts of corruption in the form of sentencing of offenders as set forth in Medan District Court's decision